Comparative study of intraoperative application of daunorubicin and conjunctival autograft in primary pterygium surgery: an interesting followup study - Sinha, Abha; Prasad, Vireshwar (International Journal of Research in Medical Sciences, 2017)
Background: The exact aetiology and pathogenesis of pterygium remains unclear but it is more common in people with excessive outdoor exposure to sunlight and wind, such as those who work outdoors. Pterygium is of great concerns to both surgeons and patients, as it has been shown to recur in up to 97% of patients within one year after surgical removal. Different adjuvant procedures like lamellar corneal graft, irradiation etc. to prevent recurrence is not encouraging. Of late a new anticancer drug named Daunorubicine (0.02%) has been used intraoperatively in pterygium surgery by one of the study with promising results. Pterygium excision with Conjunctival Autografting is very popular technique to prevent recurrence with very few side effects. This is being tried out with success in different country. Methods: The study was carried out on 60 patients who presented to the eye department at Darbhanga medical college and hospital, Laheriasarai (Bihar), India during the period from May 2005 to may 2006, & was analysed retrospectively. Efforts were made to select patients with primary fleshy pterygium. Patients selected were divided into two groups group 1 & group 2. All patients under this study were suggested to a thorough general & ocular examination. Pterygium excision in all selected cases was done under topical 4% lignocaine drop & subconjunctival injection of 2% lignocaine with adrenaline; pterygium was slowly dissected out. After the pterygium was removed from over the cornea subconjunctival dissection of the fleshy mass was done. The graft, over the scleral bed, was smoothed & spread out; the suture is done with 10-0 nylon. Post – operative management was done. The subsequent checkups were on 15th post-operative day, at 1st month, 3rd month & 6th month & same procedures were followed up to 1 year. Data was compiled in MS-Excel and checked for its completeness and correctness. Then it was analyzed. Results: Majority of patients was of age group ranged from 31 years to 50 years. 11 patients were less than 30 years of age. In group I, out of 30 eyes of 30 patients three eyes (10 %) had bilateral pterygium (both nasal and temporal). Two eyes (6.7%) had temporal pterygium. Rest 25 eyes (83.3%) had pterygium located nasally. In group II, out of 30 eyes of 30 patients two eyes (6.7%) had bilateral pterygium. Three eyes (10%) had temporal pterygium. Rest twenty five eyes (83.3%) had pterygium located nasally. Improvement of visual acuity in most of the patient after pterygium surgery. In group I, out of 30 eyes, two patients had developed recurrence, so the recurrence rate in group I is 6.6 %. In group II, out of 30 eyes, one patient had developed recurrence. So the recurrence rate in group II is 3.3%. Conclusions: The present study concluded that both the procedures are equally effective adjuncts to prevent recurrence in pterygium surgery.